The presidency in a separated system - Jones, Charles O. (Brookings Institution Press, 2005)
"Examines the organizational, political, and procedural challenges faced by postwar U.S. presidents, from Truman through George W. Bush, working in a separated system of government"--Provided by publisher
Keywords: Presidents -- United States -- History.; Separation of powers -- United States.; United States -- Politics and government.; Présidents -- États-Unis -- Histoire.; Séparation des pouvoirs -- États-Unis.; États-Unis -- Politique et gouvernement.; POLITICAL SCIENCE -- Political Process -- Leadership.; POLITICAL SCIENCE -- American Government -- General.; Politics and government; Presidents; Separation of powers; United States; Presidentschap.; Scheiding der machten.; History